ANALISA PELAKSANAAN SERTIFIKAT LAIK FUNGSI BANGUNAN GEDUNG RUSUNAWA POLITEKNIK NEGERI PONTIANAK: ANALISA PELAKSANAAN SERTIFIKAT LAIK FUNGSI BANGUNAN GEDUNG RUSUNAWA POLITEKNIK NEGERI PONTIANAK - Sovyan Arifin, Muhammad; Rizal, rizal; rasiwan, rasiwan (Jurusan Teknik Sipil Polnep, 2022)
Function-worthy Certification (SLF) is a certificate given by the Regional Government to buildings that havebeen completed and have met the requirements for the function of the building, as well as the feasibility ofpublic buildings in Pontianak City. The problem of this research is whether the owner/user of the buildingalready knows about the implementation of SLF in accordance with the law. The purpose of this study was toinvestigate the owner/user of the building knowing about SLF and to find out that the owner/user of thebuilding already knew about the implementation of SLF in accordance with the law. The method we use is tocollect data directly in the field, both physical building reliability data and supporting data for theadministration of function-worthy certificates. Based on PP No. 36 of 2005, it is necessary to follow up in theform of checking the reliability of the building as the initial basis for consideration and recommendations oneach aspect of the inspection, the issuance of a Certificate of Feasibility of Function (SLF) of buildings by theRegional Government. In the City of Pontianak, the Regional Regulation of the City of Pontianak Number 10of 2018, concerning Buildings has been issued. Pontianak City Government, West Kalimantan. The result isthe architectural reliability value of the Polnep polnep condominium building 89.7%, the polnep polneprusunawa building structure reliability value of 99%, and the reliability value of the 70.2% polnep polnepcondominium utility building.